2000
DOI: 10.1542/peds.106.6.e85
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cisapride on Corrected QT Interval, Heart Rate, and Rhythm in Infants Undergoing Polysomnography

Abstract: ABSTRACT. Objective. To evaluate the effects of cisapride, a prokinetic gastrointestinal drug, on the electrocardiographic QT interval, heart rate, and rhythm in infants during routine 8-hour polysomnography. Reported electrocardiogram (ECG) and rhythm disturbances in a small number of patients with the use of cisapride provided the impetus for this prospective study.Study Design. Two hundred fifty-two infants born at term were enrolled. Of these, 134 were on cisapride therapy for suspected gastroesophageal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…[57][58][59][60][61] This is also confirmed by general surveys in the population. Among 36 743 cisapride users in Canada and the UK, cisapride did not appear to be associated with serious rhythm disorders.…”
Section: Tolerability Of Cisapridesupporting
confidence: 60%
See 1 more Smart Citation
“…[57][58][59][60][61] This is also confirmed by general surveys in the population. Among 36 743 cisapride users in Canada and the UK, cisapride did not appear to be associated with serious rhythm disorders.…”
Section: Tolerability Of Cisapridesupporting
confidence: 60%
“…During the last couple of years, no new risk factors have been identified (see table III for established contraindications and precautions). There is little doubt that cisapride may have a QT-prolonging effect in some circumstances, [8,9,[57][58][59][60][61] as do many other drugs and clinical situations (table III). [56] Cisapride possesses Class III antiarrhythmic properties and prolongs the action potential duration, delaying cardiac repolarisation, [62] although many studies do not report an increase in duration of QTc in neonates or in older children.…”
Section: Tolerability Of Cisapridementioning
confidence: 99%
“…An association between a prolonged QTc interval in the 1st week of life and sudden infant death syndrome was reported in 1998 [17] and since 1996, various case reports have mentioned a prolonged QTc interval in association with the use of cisapride, a routinely prescribed gastroprokinetic agent [9,10]. Several prospective studies confirmed an increase in QTc interval following the use of cisapride in preterm neonates and young infants but results are inconsistent and although a relationship could be found between postnatal age, gestational age and QTc prolongation, the clinical importance remains unclear [2,3,5,6,7,8,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Several proarrhythmia risk factors have been identified: overdose or concomitant use of drugs that are metabolized through the P-450 cytochrome or prolong the Q-T interval, heart disease, electrolyte disturbances, prematurity, and newborn age [15,17]. From a review of the effects of cisapride on the QTc interval, it appears that preterm and term infants younger than 3 months of age are particularly sensitive to the cardiac effects of cisapride (table 6).…”
Section: Discussionmentioning
confidence: 99%